Предмет: Алгебра,
автор: kotik3248
Решите уравнение
(x+7)^2=(6-x)^2
(2x-3)^2=(9+2x)^2
Ответы
Автор ответа:
0
Такие уравнения решаем так:
(х+7)^2=(6-х)^2,
|х+7|=|6-х|.
1) х+7=6-х, х=-1/2;
2) х+7=-6+х, нет решения.
Ответ : - 1/2.
(2х-3) ^2=(9+2х)^2
|2х-3|=|9+2х|.
1) 2х-3=9+2х, нет решения.
2) 2х-3=-9-2х, 4х=-6, х=-1,5.
Ответ : - 1,5
Похожие вопросы
Предмет: Математика,
автор: polinagriggorevna
Предмет: Русский язык,
автор: lejlaplej
Предмет: История,
автор: tarasmukan21
Предмет: Физика,
автор: lenautochka